The Daegu Mosque and the Construction of Social Cohesion in Multicultural Korean Society - Adnan, Muhammad; Kim, Kyunghak (Pustaka Peradaban, 2025)
The construction of the Daegu Mosque in South Korea is a significant symbol of transformation, fostering understanding, social cohesion, and the social inclusion of migrants. This study examines how the mosque's construction facilitates the social integration of Muslim migrants into Korean society, particularly within the local community. Utilizing qualitative research methods, including in-depth interviews, document analysis (of pamphlets and other materials), and participant observation, this study investigates the experiences and perspectives of migrant Muslims. The findings demonstrate that the mosque plays a crucial role in mitigating prejudice, promoting solidarity, fostering a sense of belonging among migrant Muslims, and enhancing intercultural understanding, thereby contributing positively to their social inclusion. By bridging religious and cultural divides, the mosque helps strengthen social ties within the broader Korean community. The construction of the Daegu Mosque serves as a positive example of a welcoming place of worship that promotes interreligious harmony and respect, demonstrating how such spaces can foster understanding in interreligious relations. This research underscores the importance of embracing multicultural and religious identities to build more peaceful and inclusive societies.